Enhanced absorption of TiO2 nanotubes by N-doping and CdS quantum dots sensitization: insight into the structure. Issue 61 (12th October 2018) - Bjelajac, Andjelika; Petrović, Rada; Djokic, Veljko; Matolin, Vladimir; Vondraček, Martin; Dembele, Kassioge; Moldovan, Simona; Ersen, Ovidiu; Socol, Gabriel; Mihailescu, Ion N.; Janaćković, Djordje
Abstract : A simple two-step procedure to shift the absorption of TiO2 nanotubes to the visible range. Abstract : Anodization of titanium film sputtered on fluorine doped tin oxide (FTO) glass was performed to obtain highly ordered ∼2 μm long and ∼60 nm wide TiO2 nanotubes. The titania films were annealed in ammonia atmosphere to enable the doping with N. The annealing did not affect the nanotubular morphology and the porosity remained open which is a very important requirement for further deposition of CdS quantum dots. The analysis done by transmission electron microscopy (TEM) has shown that the N-doped nanotubes have a smaller interplanar distance as compared to the undoped ones, whose interplanar distance corresponded to anatase phase. This difference was attributed to the N doping and the Sn migration from the substrate, as demonstrated by energy dispersive spectroscopy (EDS) combined with electron energy loss spectroscopy (EELS). The near edge X-ray absorption fine structure (NEXAFS) analysis clearly demonstrated that also the doped TiO2 film has anatase phase. Regarding the chemical composition of the studied samples, the X-ray photoelectron spectroscopy (XPS) and synchrotron radiation photoelectron spectroscopy (SRPES) analyses have shown that N is incorporated both interstitially and substitutionally in the TiO2 lattice, with a decreased contribution of the interstitial after ionic sputtering. The shift of the valence band maximum (VBM) position for the doped TiO2 vs. the undoped TiO2 proved the narrowing of the band gap. The CdS/TiO2 films show bigger VBM shifting that can be attributed to CdS deposit. Comparing the absorption spectra of the bare undoped and doped TiO2 samples, it was noticed that the doping causes a red shift from 397 to 465 nm. Furthermore, the CdS deposition additionally enhances the absorption in the visible range (575 nm for undoped TiO2 /CdS and 560 nm for doped TiO2 /CdS films).